Sustainable re-utilization of waste materials as adsorbents for water and wastewater treatment in Africa: Recent studies, research gaps, and way forward for emerging economies - Chelangat Ngeno, Emily; Mbuci, Kinyua E.; Chaker Necibi, Mohamed; Odhiambo Shikuku, Victor; Olisah, Chijioke; Ongulu, Roselyn; Matovu, Henry; Ssebugere, Patrick; Abushaban, Almotasembellah; Sillanpaa, Mika (Environmental Advances, 2022)
Access to clean water is a fundamental human right. However, due to the rapid urbanization and industrialization in many African countries, the emergence of a plethora of new classes of water contaminants coupled with aging wastewater treatment infrastructure and technologies, access to clean water has remained elusive especially to rural communities. Additionally, most countries in Africa cannot afford the capital investment associated with advanced and specialized treatment technologies. The solution seems to be the valorization of locallysourced waste materials and their use as adsorbents, flocculants/coagulants, or photocatalysts, to be included in current and future wastewater treatment facilities. The present review presents a concise and comprehensive compilation, and critique of recent research water purification studies in Africa using waste-based adsorbents. While the abundance of industrial and agricultural wastes presents opportunity for sustainable exploitation for water treatment, several gaps warrant further research. Specifically, future research should include life cycle assessment (LCA) of the wastewater treatment plants (WWTPs) and proposed technologies, in-depth cost analysis, use of environmentally relevant concentrations in simulated studies or real wastewaters and examination of removal efficiencies for biological contaminants such as viruses, bacteria among others. Waste materials are shown to be suitable candidates for delivery of effective and techno-economic adsorbents for water purification in African countries.
Keywords: Wastewater treatment; Pollutants; Adsorption; Waste materials; Africa